The dispute about classical sociobiology - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2003)
“Sociobiology: New Synthesis” is a book written by W. O. Wilson, which in 1975 started the famous dispute about sociobiology. The dispute is the contemporary version of the old one about the nature of man. The issue concerns the factor, which determines the behaviors of living organisms, especially human beings. There were two groups who took part in that dispute. On one side, there were sociobiologists under the leadership of Wilson. On the other, there were left-wing scientists and students connected with the Sociobiology Study Group of Science for the People. In the first stage, the dispute was very intense and political, however, it soon became more content-related. The dispute is not over yet. Both sides agreed for a ceasefire, but they are ready to open it at any time.